The activity of myeloid cell-specific VHH immunotoxins is target-, epitope-, subset- and organ dependent. Issue 1 (December 2017) - Bachran, Christopher; Schröder, Matthias; Conrad, Lena; Cragnolini, Juan; Tafesse, Fikadu; Helming, Laura; Ploegh, Hidde; Swee, Lee
Abstract The central role of myeloid cells in driving autoimmune diseases and cancer has raised interest in manipulating their function or depleting them for therapeutic benefits. To achieve this, antibodies are used to antagonize differentiation, survival and polarization signals or to kill target cells, for example in the form of antibody-drug conjugates (ADC). The action of ADCin vivo can be hard to predict based on target expression pattern alone. The biology of the targeted receptor as well as its interplay with the ADC can have drastic effects on cell apoptosis versus survival. Here we investigated the efficacy of CD11b or Ly-6C/Ly-6G-specific variable fragments of camelid heavy chain-only antibodies (VHH) conjugated toPseudomonas exotoxin A to deplete myeloid cellsin vitro andin vivo . Our data highlight striking differences in cell killingin vivo, depending on the cell subset and organs targeted, but not antigen expression level or VHH affinity. We observed striking differences in depletion efficiency of monocytes versus granulocytes in mice. Despite similar binding of Ly-6C/Ly-6G-specific VHH immunotoxin to granulocytes and monocytes, granulocytes were significantly more sensitive than monocytes to immunotoxins treatment. Our results illustrate the need of early, thoroughin vivo characterization of ADC candidates.